Unveiling the Shadows: Exploring the Roles of the Dark Web and Encrypted Messaging Apps in Facilitating Online Terrorist Networks - Ogele, Eziho Promise (Journal of Strategic and Global Studies, 2025)
The paper examines the pivotal roles of the Dark Web and encrypted messaging apps in enabling online terrorist networks. These platforms have become essential tools for extremist groups, empowering them to communicate, coordinate, and share intelligence securely. The Dark Web, a hidden portion of the internet, provides a secure conduit for terrorist organizations to emerge, operate, and coordinate activities anonymously. This digital haven enables terrorists to share resources, plan operations, and execute attacks as part of their secret operations strategy. Encrypted messaging apps, such as Telegram and WhatsApp, offer an additional layer of security, allowing terrorists to send messages anonymously and evade detection. These apps create a veil of secrecy, making it challenging for counter-terrorism agents to identify and track extremist activities. The convergence of the Dark Web and encrypted messaging apps poses a significant threat to global security. The unification of these technologies enables terrorists to operate undetected, making it increasingly difficult for law enforcement agencies to counter their activities. The paper adopted social network theory as its theoretical underpinning. The paper was elicited through a secondary data-gathering technique. They revealed that the Dark Web and encrypted messaging apps have been essential to the function of online terrorist organizations and also used as a means of dissemination of propaganda, radicalization, fundraising, training, communication, coordination, share information, among others. The paper recommends amongst others, that Law enforcement operations should track down and bring to a halt the Dark Web marketplaces as well as encrypted messaging apps used by terrorists.